Aerial photoluminescence imaging of PV modules - Doll, Bernd; Wittmann, Ernst; Lüer, Larry; Buerhop-Lutz, Claudia; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Conference Record of the IEEE Photovoltaic Specialists Conference, 2023)
On-site imaging of photovoltaic systems requires methods that are high-throughput, low-cost and contact free for commercial relevance. Photoluminescence imaging satisfies these requirements, but it has so far not been used for aerial imaging due to a lack of a drone-mounted system. In this study, we present first results captured by our in-house developed PLAI (photoluminescence aerial imaging) setup. The setup consists of a hexacopter aerial drone equipped with an illumination unit and a near infrared camera. The unit is capable of partially illuminating full size modules at night and capturing the photoluminescence response. We show that the setup can be used to detect and identify defects such as cracks and potential-induced degradation with high levels of confidence.
CRIS-Team Scopus Importer:2024-12-16

The Voltage-Ear – An Anomaly in photovoltaic systems with undersized inverters - Wittmann, Ernst; Buerhop-Lutz, Claudia; Christlein, Vincent; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (IEEE Photonics Journal, 2024)
This study presents a phenomenon in photovoltaic field installations we call voltage ear. PV installations exhibit the voltage ear under specific conditions where modules generate more power than the inverter can handle. When inverters exceed their power limit it results in inverter clipping, and the solar modules are regulated to operate at a voltage above that at maximum power. This kind of voltage rise leads to a specific pattern in the monitoring data – the voltage ear. In the present study, data from a solar park in France was analyzed. This park featured a high rate of inverter malfunctions, including overheating and fires, resulting in an estimated 5% failure rate and, ultimately, in a complete replacement of inverters. An automated analysis of the monitoring data revealed 32.000 occurrences of excess voltage in 1.65 million data points (2%). Instances of the phenomena were detected and segmented using a K-means sorting algorithm, which yielded a perfect recall value. Analysis of the identified voltage ear conditions showed, that it occurs predominantly during seasons of high irradiance and cool temperatures. Excess voltages of up to 161 V in single strings were observed, increasing the probability for PID and inverter damage. The direct yield loss due to deviation from maximum power point was between 0.02% in January and 0.9% in June. We assume, that the voltage ear is a symptom of system design issues that can result in malfunctioning of inverters and hope that it will be useful as an indicator for identifying design and operation issues.<br
Keywords: Inverters; Ear; Voltage measurement; Monitoring; Voltage control; Temperature measurement; Current measurement; PV field inspection; monitoring data; voltage ear; K-means clustering; inverter failure